Elements of reformist thought between Mullah Muhammad al-Kuyi and Sheikh Muhammad al-Khal - Ahmed, Dr. Saadoun Hussein (Sulaimani Journal for Humanities, 2023)
At the beginning of the twentieth century, voices in support of reform rose in the Muslim community. There were scholars and enlighteners from different parts of the Islamic world calling for the necessity of reform in the field of religious thinking and the social system. Kurdish society was not far from that movement, and its scholars were not oblivious to the necessity of making radical changes in Religiosity and the prevailing lifestyle in society. Sheikh Mulla Muhammad al-Kuyi and Sheikh Muhammad al-Khal were advocates of the reform movement in Kurdish society. They made great efforts in writing and delivering sermons, and they tried tirelessly to bring about changes in the way of religiosity and lifestyle. They began researching topics related to women, education, and education, please. Creating a change in the thinking of the Kurdish individual and thus making progress in Kurdish culture regarding these issues, according to their vision, the Kurdish society will not be able to take a step towards progress except by bringing about changes and reforms in those files that were mentioned.
Keywords: Elements; reformist; Mullah Muhammad; alKhal